Response of Fungicides and Antibiotics Against Anthracnose of Poplar Caused by Colletotrichum graminicolum - Singh, Dipak; Chandra, J. P.; Singh, A. B. (Indian Forester, 1999)
Anthracnose of Poplar caused by Colletotrichum graminicolum is a serious disease in Tarai region of Uttar Pradesh. The present investigation were undertaken to study the screening of fungicides and antibiotics against the pathogens under in-vitro conditions. Hundred per cent inhibition of C. graminicolum was recorded in Bavistin (50 ppm and onward) and Topsin-M in 10 ppm and above. Aureofungin was found highly effective against this fungus in reduction of radial growth as well as spore germination.